أسباب الثأر وأخطاره في الصعيد المصري - محمد، أسماء محمد إسماعيل (جامعة أسيوط - كلية الخدمة الاجتماعية, 2020)
ولقد أصبحت مشكلة الثأر واحدة من المشكلات الاجتماعية التي تواجه المجتمعات الإنسانية بوجه عام، والصعيد المصري بوجه خاص، ومن ثم سوف يتناول هذا البحث مشكلة الثأر في الصعيد المصري من خلال عرض لمحة من مفهوم الثأر، وخصائص نظام الثأر ومحدداته، البعاد القانونية والثقافية للأخذ بالثأر، القواعد التي تحكم ظاهرة الأخذ بالثأر، الإجراءات والتقاليد المتبعة لجريمة الأخذ بالثأر، دور المرآة في التحريض على الثأر، الأسباب والعوامل المؤدية إلى الثأر، كيفية مواجهة جريمة الأخذ بالثأر.
The problem of revenge has become one of the social problems facing human societies in general, And the Egyptian Upper Egypt in particular. Hence, this research will address the problem of revenge in the Egyptian level through an overview of the concept of revenge, The characteristics and determinants of the vengeance system, the legal and cultural dimensions of vengeance, the rules governing the vengeance phenomenon, the procedures and traditions used for the vengeance crime, the role of the woman in inciting vengeance, the reasons and factors leading to vengeance, how to confront the crime of vengeance.
Keywords: المشكلات الاجتماعية -- جرائم القتل -- الثأر -- مصر